Case Report: The lost art of cisterna magna puncture—teaching video - Weiss, Viktor; Harsany, Michal; Brichta, Jaroslav; Kojan, Martin; Herzig, Roman; Cervenak, Vladimír; Filip, Pavel; Aulicky, Petr (Frontiers in Surgery, 2025)
The early 20th century saw the emergence and fall of cisterna magna puncture as a therapeutic and diagnostic tool, purportedly offering distinct advantages over lumbar puncture. However, the renewed interest in this procedure as a potential access point in intrathecal gene therapy indicates that it may not be completely forgotten. In light of the limited reports and the virtual loss of practical expertise with this procedure among specialised clinicians, this instructional video is offered as a valuable resource for clinicians or researchers not only in diagnostic settings, but also as an access to the central distribution point of cerebrospinal fluid with therapeutical intents in the future, as envisaged by medical pioneers a century ago.